2019
DOI: 10.1017/s0007114519000011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dyslipidaemic diet induces sex-specific alterations in intestinal function and lipid metabolism in rat offspring

Abstract: This study investigated the effects of a maternal dyslipidaemic (DLP) diet on lipid metabolism, microbial counts in faeces and hepatic and intestinal morphology in rat offspring with respect to sex during different phases of life. Wistar rats (dams) were fed a control (CTL) or DLP during gestation and lactation. After weaning, CTL and DLP offspring were fed a standard diet. The effects of a maternal DLP on body composition, biochemical parameters, faecal microbiota and intestinal and hepatic histomorphometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Posteriorly, pregnant rats were allocated to a control group (n = 4) and received a diet prepared according to the American Institute of Nutrition -AIN-93G; or a HFHC group (n = 4) that received a diet (Table 1) purchased from Rhoster Company (Araçoiaba da Serra, São Paulo, Brazil) during pregnancy and lactation period as previously described. 1,16,17 After weaning (postnatal day 21), male rat offspring (CTL, n = 16 and HFHC, n = 15) were weighted, housed separately (3−4 per cage), and had free access to a commercial diet (Presence Purina, Paulínea, São Paulo, Brazil) and water ad libitum up to 100 days of age. At that age, the experimental groups were randomly formed with one to two rats from each litter.…”
Section: Ethical Aspects and Experimental Designmentioning
confidence: 99%
“…Posteriorly, pregnant rats were allocated to a control group (n = 4) and received a diet prepared according to the American Institute of Nutrition -AIN-93G; or a HFHC group (n = 4) that received a diet (Table 1) purchased from Rhoster Company (Araçoiaba da Serra, São Paulo, Brazil) during pregnancy and lactation period as previously described. 1,16,17 After weaning (postnatal day 21), male rat offspring (CTL, n = 16 and HFHC, n = 15) were weighted, housed separately (3−4 per cage), and had free access to a commercial diet (Presence Purina, Paulínea, São Paulo, Brazil) and water ad libitum up to 100 days of age. At that age, the experimental groups were randomly formed with one to two rats from each litter.…”
Section: Ethical Aspects and Experimental Designmentioning
confidence: 99%
“…The LPS linked to gut dysbiosis may contribute to inflammation, oxidative stress and sympatho‐excitation via a toll‐like receptor 4 activation . A recent study from our laboratory demonstrated that the consumption of a dyslipidaemic diet during the gestational and lactational period provoked severe damage to the intestinal parenchyma and faecal microbiota in both dams and offspring . Our next step will be to test whether targeting microbiota with probiotic intervention or reducing oxidative stress and inflammation during the periconceptional period prevents or delays the onset of cardiometabolic disorders in adult offspring.…”
Section: Discussionmentioning
confidence: 99%
“…As the equivalent impedances depend on the frequency, the roots must be calculated starting with s = 0 and repeating the iteration up to s → s * with negligible error. From the EFR reactance measurements obtained in the laboratory [18] for a particular frequency (60 Hz), it is possible to extrapolate to other frequencies by calculating, for a given…”
Section: Control Through Feedback Linearizationmentioning
confidence: 99%
“…The EFR design parameters were obtained from Pinheiro et al [18] (cf Table 1). In order to satisfy a load of 5 kW at a wind speed of 7 m/s and an armature power (design chosen) of 4 kW, the S L I P algorithm was applied to these numbers, resulting in the set of values in the second column of Table 4.…”
Section: Design Parametersmentioning
confidence: 99%